'... A 40‐Year‐Old Black Man Made the Point to Me': Everyday Knowledge and the Performance of Leadership in Contemporary British Politics. (11th May 2012) - Atkins, Judi; Finlayson, Alan
<x xml:space="preserve">Abstract</x> In this article we demonstrate the application of rhetorical political analysis in the study of political communication and political ideas and ideologies. Taking the rhetorical use of anecdotes as a case study, we find that their use by mainstream party leaders in Britain has proliferated markedly since the mid‐1990s. Drawing on examples from speeches by leaders of all three main parties, we show how these stories are employed as a form of argumentative proof that relies significantly on the elevation of 'everyday' experience and knowledge above expert or technical knowledge. We argue that this reflects a more general 'valorisation of lay knowledge' and, moreover, that it is indicative of a form of populist ideology.